2019
DOI: 10.16965/ijar.2018.433
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Branching Pattern of Femoral Artery

Abstract: Background: During clinical procedure to prevent damage, anatomical knowledge of the common femoral artery, profunda femoris artery (PFA) and the circumflex arteries is essential.Material and Methods: Present study was done on 40 lower limbs (20 left and 20 right) in Government Medical College and Hospital, Chandigarh. Dissection was done as per the guidelines in Chunighums.Aim: Present study was done to discuss variations in branching pattern of FA, PFA and also their embryological and clinical significances.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…14 A study also reveals lower termination of brachial artery at the level of radial tuberosity in 8.6% of upper limbs. 8 The mean length of brachial artery observed in this study was 23.62 ± 2.98 cm. The mean length values revealed by other studies are higher (27.1 cm and 26.29 cm respectively) than that of the present study.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…14 A study also reveals lower termination of brachial artery at the level of radial tuberosity in 8.6% of upper limbs. 8 The mean length of brachial artery observed in this study was 23.62 ± 2.98 cm. The mean length values revealed by other studies are higher (27.1 cm and 26.29 cm respectively) than that of the present study.…”
Section: Resultsmentioning
confidence: 50%
“…[4][5][6][7] Slightly varying from current study, other studies showed prevalence of higher bifurcation of brachial artery ranging from 10% to 15%. [8][9][10][11][12][13] In contrast to these findings, finding from another author demonstrated greater prevalence (27.6% ) of higher termination of brachial artery. 14 A study also reveals lower termination of brachial artery at the level of radial tuberosity in 8.6% of upper limbs.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A simple ultrasound examination can detect the anomaly and allow the diameter assessment for clinical decision-making regarding access creation [47]. According to Rodríguez-Niedenführ et al [2] and Singer [3], this type of anomaly is due to the failure of formation of the communicating branch between the superficial brachial artery and axial artery at the level of the elbow and thus superficial brachial artery did not disappear but continues as radial artery (Table 2) [37,[48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…3 There are many articles reporting variation of division of brachial artery at different levels, but mid arm variation i.e, bifurcation at the level of insertion of coracobrachialis muscle is of common occurrence. 4 Normal vascular development including patterning of the blood vessels is influenced by local hemodynamic factors. Altered hemodynamic environment may give rise to variant patterning of blood vessels.…”
Section: Introductionmentioning
confidence: 99%